Evaluation of children with acute gastroenteritis in Konya region - Fatih Akın; Ahmet Osman Kılıç; Abdullah Yazar; Hussein M.h. Atwan (SERNEV, 2021)
Introduction: Acute gastroenteritis is a major cause of pediatric morbidity and mortality around the world. It remains a frequent reason for infection-related admissions to emergency units among all age groups. Epidemiologic knowledge about etiology of gastroenteritis in a certain area allows early and correct diagnosis. The current study aimed at evaluating the prevalence of bacterial, viral, and parasitic pathogens in children with gastroenteritis who admitted to pediatric emergency unit. Methods: The demographic, clinical and laboratory data of 450 children with acute gastroenteritis, within the age range of 0 months to 18 years who admitted to Pediatric Emergency Department of Meram Faculty of Medicine from September 2018 to September 2019 were retrospectively analyzed.Results: While 31.10% of the patients had etiological agents, 68.90% of the patients could not be identified. The identified pathogens were 2.10% bacteria, 82.20% virus, 15.70% parasite. The most common pathogen was Rotavirus with a rate of 72.90%. This was followed by E. histolytica with 15.00% and Adenovirus with 9.30%. Rotavirus was most frequently detected at the age of 2 years, and E. histolytica was most frequently detected at the age of 5 years. Rotavirus was most common in the winter season [33.7%]. 7.10% of the patients were hospitalized. The average length of hospital stay was 3.34 ± 2.19 days.Conclusion: Rotavirus, E. histolytica and Adenovirus were the most prevalent agents of diarrhea in children aged 0 month to 18 years who admitted to emergency unit in this study.